Histological and immunohistochemical characteristics and p16 status studied by FISH in six incidentally detected cases of well-differentiated papillary mesothelioma of the peritoneum - Fumiyoshi Fujishima; Sachiko Konosu-Fukaya; Kazuki Nabeshima; Keely M McNamara; Kazuhiro Sakamoto; Junko Sakurada; Hironobu Sasano; Yasuhiro Nakamura (Wolters Kluwer Medknow Publications, 2021)
Well-differentiated papillary mesothelioma (WDPM) is an uncommon mesothelial neoplasm, which is generally regarded as benign or indolent in terms of its clinical behavior. However, details about WDPM have remained relatively unknown. Therefore, in this study, we examined six incidentally detected cases of WDPM of the peritoneum. All six cases were surgically excised, without any additional therapeutic measures. None of the cases showed recurrence. All six cases presented single lesions and the tumor sizes ranged from 2 to 10 mm. Histologically, all six cases exhibited papillary proliferation of cytologically bland mesothelial cells with a fibroconnective tissue core. One of the cases (Case 6) presented small invasive foci in the stalk. The tumor cells were immunohistochemically positive for mesothelial markers and negative for GLUT-1, p53, and CD146. The Ki-67 labeling index of the tumor cells was lower than 5% at the hot spots. All samples were BAP1-positive. None of the samples presented p16 homozygous deletion, as assessed by fluorescence in situ hybridization (FISH). None of the patients deceased due to WDPM. However, in Case 3, death occurred due to pancreatic cancer. The results of this study indicate the importance of analyzing immunohistochemical markers and p16 status to diagnose WDPM accurately.